Partido Social Cristão: organização e distribuição do poder - Cassotta, Priscilla Leine (2019)
The decision-making process within political parties is one of the most recurrent themes in the debate on the institutionalization of the party system. In this sense, the objective of this research is to analyze the organizational transformations of the Christian Social Party - PSC, with emphasis on the internal changes promoted by the party elites and their possible consequences and conflicts, since this party concentrates Catholic and Evangelical Christians, often with conflicting interests. In recent years, throughout Latin America it is possible to observe the reemergence of conservative forces in the political scenario. On this occasion, in Brazil, evangelicals come to endorse a conservative agenda, equipped with a moralistic discourse in defense of Christian precepts and in favor of the traditional family. Thus, we try to answer the following question: how does the distribution of internal power in the PSC occur, from changes in its leadership? What are the organizational consequences of this change? Our general hypothesis is that from changes of the top leaders, influenced by the external environment, the PSC began to align its political appeal with evangelical Christianity, changing its hunting territory and becoming more conservative. Therefore, the bonds and resources derived from this Christian segment became more important to the party's organizational survival.